EFFECTIVENESS OF KINETIC TREATMENT OF OSTEOPOROSIS - Florian BENEDEK (Editura Universitatii Transilvania din Brasov, 2020)
The main purpose we want to highlight in this study is the treatment of the recovery of osteoporosis by kinetic means, investigations used to put diagnosis, the effectiveness of its treatment, and awareness of the importance of physical therapy in this condition. In order to carry out this work we left the hypothesis that by using physiotherapy and means of physical therapy we will have positive effects in the case of recovery of the patient with osteoporosis. In conclusion, I can say that I was able to show how effective the recovery treatment for osteoporosis is and that this condition can be improved and stopped with the help of physical therapy and physiotherapy, preventing the appearance of fractures.